ANALYSIS VISIBILITY PARK AND RIDE TANGERANG DISTRICT (case study Cisauk Station) - Lestari, Ayu; Murtejo, Tedy; Chayati, Nurul (ASTONJADRO, 2021)
Tangerang Regency is an area located in Tatar Pasundan, Banten Province, Indonesia. This area is located 30 km west of Jakarta and 90 km southeast of Serang. With an annual population growth rate of ± 2.15 percent, the total population of Tangerang Regency in 2020 is ± 2,838,621 according to the Central Statistics Agency (BPS) of South Tangerang Regency. South Tangerang Regency which has an area of 959.6 kilometers. This research was conducted to determine the feasibility level of the Park and Ride development plan in Tangerang Regency. Traffic counting surveys and interviews were carried out on main road sections which were then processed using Microsoft Excel to determine the parking accumulation until the fluctuation of motorbikes and cars was known. Furthermore, the interview data is processed to determine the amount of public interest in the development of Park and Ride which is reviewed based on gender, age, trip duration, trip intent, parking duration, monthly fuel expenditures, desired parking rates and those who agree to use Park and Ride when the survey was conducted. at 06.00-21.00 WIB on the road in the Cisauk Station area. From the results of processing this data using Microsoft Excel, it was found that the characteristics of Park and Ride facilities users and also the number of users of Park and Ride facilities for motorbikes were 2349, while for cars of 272 with a plan age until 2021, this proves there is a need for increased interest in motorbikes. Park and Ride development at Cisauk Station, Tangerang Regency.